2010
DOI: 10.1097/qad.0b013e32833c93ce
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation, apoptosis, and Treg activity are associated with persistently reduced CD4+ T-cell counts during antiretroviral therapy

Abstract: Lack of CD4 recovery in individuals in whom ART suppresses HIV replication is associated with complex immune alterations. Immune activation, likely driven by altered gut permeability and resulting in augmented Treg activity could play a pivotal role in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 49 publications
8
94
1
3
Order By: Relevance
“…+ T cell nadir and a poor immunological response to HAART [27,28,39,41,42]. In particular, Mendes-Lagares et al have pointed out the role of Tregs in the control of naive CD4…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…+ T cell nadir and a poor immunological response to HAART [27,28,39,41,42]. In particular, Mendes-Lagares et al have pointed out the role of Tregs in the control of naive CD4…”
Section: Discussionmentioning
confidence: 99%
“…We observed that effector and terminal effector Tregs were increased significantly in iIR compared to cIR, which was never pointed elsewhere. Very few data are available concerning those Treg subsets in HIV-infected patients [39,50]. Effector Tregs have been studied in the peripheral blood mononuclear cells of 18 aviraemic patients with a good immunological response to HAART [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV-infected individuals receiving cART continue to have a significantly shorter life expectancy, even in settings of advanced medical care (1), and they experience higher rates of non-AIDS comorbidities such as cardiovascular disease and non-AIDS cancers (2-5), many of which have an inflammatory etiology and may be related to continuing immunodeficiency (5). The success in reconstituting a functional immune system, defined by restoration of CD4 T cell counts following cART, is limited by immune activation and associated with pre-cART endotoxemia (6,7).…”
mentioning
confidence: 99%